Efficacy evaluation of denosumab in the treatment of patients with postmenopausal osteoporosis at high risk of fracture - Jing ZHOU; Xingyun HOU; Tingting LIU; Jiaoyang ZHENG (Zhongguo Linchuang Yixue)
ObjectiveTo explore the difference of efficacy and safety between denosumab and zoledronic acid in the treatment of patients with postmenopausal osteoporosis (PMOP), and to optimize the medication regimen for PMOP patients. MethodsA total of 123 PMOP patients with high risk of fracture at the Second Affiliated Hospital of Naval Medical University from September 2021 to March 2024 were selected and randomly divided into two groups: the denosumab group (n=63) and the zoledronic acid group (n=60). Both groups underwent one-year treatment and follow-up, bone metabolism indexes, lumbar vertebrae, femoral neck, and total hip bone mineral density (BMD) were monitored, and any adverse reactions were documented. ResultsAfter treatment, the lumbar vertebrae and total hip BMD of patients in the denosumab group and the zoledronic acid group were significantly improved (P＜0.05); the femoral neck BMD of patients in the zoledronic acid group was also significantly improved (P＜0.05). The improvement of lumbar vertebrae BMD in the denosumab group was significantly better than that in the zoledronic acid group, while the improvement of femoral neck and total hip BMD in the zoledronic acid group was significantly better than that in the denosumab group (P＜0.05). Bone metabolism indicators were significantly improved in both groups (P＜0.05), and no significant liver and kidney dysfunction were observed. A total of 7 patients in the zoledronic acid group had mild adverse reactions and 5 patients in the denosumab group had mild adverse reactions. ConclusionsDenosumab significantly increased lumbar vertebrae BMD and improved bone metabolism markers in PMOP patients, thus reducing risk of fracture and demonstrating good safety.